Political Capitalism. Issue 1 (10th May 2023) - Levinson, Marc
Abstract : "Capitalism, " etymologists say, is rooted neither in Adam Smith nor in Karl Marx but in The Newcomes, a long-forgotten novel by William Makepeace Thackeray, in which a fallen French nobleman regains his dignity when the rising price of railway shares restores his "sense of capitalism" (Project Gutenberg ebook edition, p. 1016). It's one of those you-know-it-when-you-see-it kinds of words, meaningful mainly when set against "socialism, " a word first used in the 1820s to describe collective ownership of property. Capitalism has taken on all sorts of meanings since Thackeray coined the term in 1854, describing everything from the repression of miners by late-nineteenth-century robber barons to the venture-capital-fertilized blossoming of Silicon Valley. The three histories discussed in this essay all address its meaning in the modern world economy. None believes that future capitalism will be like capitalisms past.